Functional Activation Mapping of Scar-Related Ventricular Tachycardia Substrate - Volponi Lovatto, Carlos; Vassallo, Fabricio; Serpa, Eduardo; Simões Jr, Aloyr; Carloni, Hermes; Lemos, Christiano; Batista Jr, Walter; Hespanhol, Dalton; Nogueira, Alberto; Zeni, Rafael; et al. (JOURNAL OF CARDIAC ARRHYTHMIAS, 2020)
The optimal method to identify the arrhythmogenic substrate of scar-related ventricular tachycardia (VT) is unknown. Sites of activation slowing during sinus rhythm (SR) often co-localize with the VT circuit. This is a report of two scar related VT substrate mapping using a strategy of voltage-independent approach.